"Producing Human Capital": A Critical Discourse Analysis of Title II of the Workforce Innovation and Opportunity Act (WIOA). Issue 3 (August 2019) - Shin, Jaran; Ging, Liz
Historical and legislative evolutions of education policy have repurposed federally funded adult education programs in the United States. The 2014 passage of the Workforce Innovation and Opportunity Act (WIOA) has considerable repercussions for everyone involved in the field because it controls the funding, assessment, and structure of these programs. Using critical discourse analysis, this study examines the public law and a Program Memorandum from the federal government. It demonstrates how the language used in the documents characterizes Title II of WIOA (the Adult Education and Family Literacy Act), the goals of adult education, eligible adult learners, and the process by which programs are held accountable for federal funding. The findings show the ways in which Title II tactically legitimizes the U.S. government's neoliberal capitalist desire within a democratic society: The idealistic language of opportunity acts as a camouflage for the further infiltration of market-oriented practices into the public sector.